Modeling foot rockers via functional calibration for use in clinical gait analysis - Salami, Firooz; Campos, Sarah; Musagara, Arik Rehani; Wolf, Sebastian Immanuel (Gait & posture, 2024)
Background - Goal of this work is a quantitative description of Jacquelin Perry’s rocker concept by locating the position of the heel rocker and the forefoot rocker within segments of the foot via functional calibration. - Methods - Two functional calibration tasks with the foot in ground contact were performed by ten typical developed adults and foot marker motion was captured. After applying a least-square method for constructing foot segments, their motion relative to the floor was analyzed via a functional algorithm. Resulting reference positions - namely the heel rotation center and the metatarsal rotation axis - were calculated. Further, the repeatability of the method and variability of outcome within the cohort was tested. - Results - The heel rotation center is located substantially posterior (25mm) and slightly more inferior (5mm). to the midpoint of the two markers placed medially and laterally on the calcaneus. Repeated measures reveal a variation of this location around 5mm. The forefoot center is slightly more medial to the “toe marker” (DMT2) and substantially more inferior (19mm). The metatarsal rotation axis is slightly tilted in the frontal and transverse plane against the metatarsal line given between markers on MT1 and MT5 with small variation in repeated measures (1-2°). - Significance - The determination of heel rotation center and the metatarsal rotation axis relative to foot segments can be determined with good repeatability and their location meet the intuitive expectation. Since they have a direct biomechanical meaning in the foot roll-over process in gait, they may be used for a more functionally oriented definition of foot segments potentially improving the calculation of foot kinematics and kinetics in future work.